Constrained distributed consensus control of homogeneous vehicle platoons with bidirectional communication - Gaagai, Ramzi; Horn, Joachim (Control engineering practice, 2023)
•A nominal distributed consensus controller for homogeneous vehicle platoons that considers the spacing errors with both the predecessor and the follower.•Input-to-state stability of the closed-loop platoon dynamics is proven through a Lyapunov approach.•String stability properties of the nominal controller are analyzed.•The nominal distributed controller is fed into an online optimization problem derived from control barrier functions to calculate the constrained control input that satisfies state and input constraints that take into account the constraints of the vehicles. Vehicle platooning is deemed a promising solution to improve traffic safety, reduce fuel consumption and increase traffic throughput and road capacity. Road throughput can be increased by driving at small inter-vehicle distances. Adjusting the spacing with both the preceding and the succeeding vehicles using bidirectional communication can potentially improve the platoon cohesiveness and is crucial when considering the synchronized merging scenario. In this paper, a distributed consensus controller is presented which relies on bidirectional platoon communication. To take into account the constraints of the system state and input constraints are implemented using control barrier functions via linear quadratic programming. Along with the consensus-based controller synthesis, platoon stability proof and string stability analysis, effectiveness of the controller is verified in a simulation study.